3SSC-A-Based Step-Down DC–DC Converters: Analysis, Design and Experimental Validation - Souza, Lucas Carvalho [UNESP]; Silva, Luciano de Souza da Costa e; Seixas, Falcondes José Mendes de [UNESP]; Arenas, Luis De Oro [UNESP] (MDPI, 2022)
This paper proposes two non-isolated step-down DC–DC converters based on the type-A three-state switching cell (3SSC-A), resulting in an alternative to the buck and buck-boost classical converters, respectively. The proposed topologies are part of a group of unexplored converters that employ the 3SSC-A, which has the advantages of 3SSC-based converters, such as high power density, reduced current stress on the semiconductors and suitable thermal loss distribution. In this regard, a complete static analysis is performed, including a detailed study of all semiconductor voltage and current efforts and developing loss models for each one. Moreover, by using simulation models, AC sweep analyses validate the dynamic frequency response of each converter’s small-signal models, and PI-based output–voltage closed-loop controllers are duly designed. Finally, the topologies are experimentally validated through the implementation of adequately designed prototypes, achieving efficiency values greater than 91% under several output power rates varying from 50% to 100%.
Keywords: 3SSC type-A; buck converter; buck-boost converter; DC–DC converter; three-state switching cell (3SSC)